THE IMPORTANCE OF GRANDPARENTS FOR THE THIRD GENERATION IN A MULTIGENERATIONAL FAMILY - Katarzyna Olewniczak (Borys Grinchenko Kyiv Metropolitan University, 2021)
Despite the changes in the model of a modern family, extended families are still functioning. Their role and functions are significant due to intergenerational contacts, based on interaction. The subject of the considerations undertaken in this study is the importance of the third generation in the life of the first one in the cognitive, behavioral, emotional and socio-economic spheres of a family. The grandparents' importance for their grandchildren is related to the mutual benefit and pleasure from the presence of the closest people in life.